تقييم برامج رعاية الاعاقة العقلية بمنطقة الباحة في ضوء معايير الجودة - محمود احمد القصاص, خضر (جامعة الوادي University of Eloued, 2018)
تقييم برامج رعاية الاعاقة العقلية بمنطقة الباحة في ضوء معايير الجودة الباحث الدكتور خضر محمود القصاص جامعو الباحة المملكة العربية السعودية ملخص الدراسة: هدفت الدراسة إلى التعرف على تقييم برامج رعاية المعاقين عقليا بمنطقة الباحة في ضوء معايير الجودة، تكونت عينة الدراسة من (111) معلما ومشرفا بمدارس رعاية المتخلفين عقليا في منطقة الباحة المطبقة لبرنامج رعاية المعاقين عقليا والتابع لإدارة التربية والتعليم بمنطقة الباحة، وتم استخدام الاستبانة كأداة لتقييم برامج رعاية المعاقين عقليا بمنطقة الباحة في ضوء معايير الجودة والتي تضمنت محورين متعلقة بمتطلبات تطبيق الجودة ومدى تحققها في برامج رعاية المتخلفين عقليا، وقد تم تطبيق الاداة في الفصل الدراسي الأول للعام الدراسي 1437/1438هـ. وتوصلت الدراسة إلى النتائج الآتية: يوجد درجة كبيرة من المتطلبات المتعلقة بتوفر معايير الجودة في برامج رعاية المعاقين عقليا بمنطقة الباحة مستوى الإدارة التربوية والإدارة المدرسية، كما يوجد مستوى كبير من تحقق معايير الجودة ببرامج رعاية المعاقين عقليا بمنطقة الباحة على مستوى الإدارة التربوية والإدارة المدرسية. The current study was conducted to evaluate the programs of mental retardation in Al-Baha region in light of the quality standards. The analytical descriptive approach was used. The sample of the study consisted of (111) teachers and supervisors in schools that included mental retardation programs in AlBaha region. A questionnaire was prepared by the researcher as a tool for assessing mental retardation programs in Al-Baha. The reliability and validity indexes were extracted for the questionnaire, which included two domains related to the requirements of the application of quality standards in the programs and the contribution of these requirements in enhancing MR programs. The questionnaire was applied in the second semester of the academic year 1437/1438. The results of the study indicated that the of requirements related to the application of quality standards in the mental retardation programs in the Al Baha region was available with a high degree. The contribution of quality standards in enhancing the programs of mental retardation in Al-Baha was also high. In the light of the results, the study recommended the necessity of activating quality standards in all special education programs to improve its outcomes.
مقال
Keywords: برامج المتخلفين عقليا؛ تقييم؛ معايير الجودة; Assessment; programs; mental retardation; quality standards